ANALYSIS OF SALES STRATEGY OF SMALL TRADERS AT THE MOUNT GALUNGGUNG TOURIST ATTRACTION - Yusuf, Ade (Nusantara Journal Of Management Business (NUMABI), 2025)
Study This aim For know 1) Profile trader small at Mount Galunggung , 2) How much good sales strategy trader small at Mount Galunggung .Method Research used _ in study This is method descriptive qualitative . Data used in study This namely primary and secondary data .Research results show that : 1) Profile trader small sell product goods and services , 2) Sales strategy trader small at Mount Galunggung is very good , 3) Research results showing results recapitulation about indicator strategy Sales , got a total score of 642 is on point 630 – 750 is classified as very good and has score highest in statement number 4 and number 7 with score 69. Meanwhile very low value contained in the statement number 5 with score 60. In whole based on results on that sales strategy trader small in Mount Galunggung on the very good classification .